A QUALITATIVE INQUIRY TOWARDS ENHANCINGNIVERSALITIES’ EFFECTIVENESS IN NIGERIA - David Jimoh Kayode, Suraiya Rathankoomar Naicker (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The role of the university towards the development of individuals as well as the society has remained the focus of every university stakeholders and, as such, becomes imperative in making sure that the university achieves its roles for which it was created to meet. This study was carried out to findout how university education in Nigeria can be enhanced towards achieving its stated goals. This study adopted a generic qualitative design to collect data through semi-structured interviews from eight participants, including a deputy vice-chancellor, deans, head of departments, and lecturers that were purposively selected. Data collected were analysed using thematic analysis with Nvivo (version 10). The findings of this study revealed that university effectiveness couldbe enhanced through increased funding, policy and institutional reforms. The results from this study imply that government alone cannot strengthen the effectiveness of the university system in Nigeria, and as such, all stakeholders have some roles to play.